Pirolisis Kayu Cemara (Casuarina Equisetifolia) Menjadi Bio-Oil Dengan Menggunakan Katalis NiMo/Lempung - Hade Karimata; Syaiful Bahri; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The basic of national energy problem this era is consumtion of fossil energy that increase rapidly which not equal with source of fossil energy itself. Requirement for the source of energy which increasing and petroleum reserve as source of primary energy which continuing attenuate to become the main reason for the importance of searching for alternative energy sources instead of petroleum. Biomass specially pine wood only considered as waste that pollutes the environment, whereas the pine bark is biomass that can be processed to become alternative energy that is bio-oil. Bio-oil can be produced through pyrolisis process using catalyst NiMo/clay. This research aim to study the effect of the ratio of amount of catalyst to biomass which have variation of 3%, 6% and 9% w/w respectively and also the effect of NiMo metal consentrate on clay equal to 0%, 1%, 2% and 3% w /w respectively of the yield bio-oil produced. In this research, pine bark biomass as muches 50 grams with particle size of -100+200 mesh, silinap 500 ml, and catalyst NiMo/clay placed into pyrolisis reactor. Process of pyrolisis is conducted at temperature 320 oC and stirring speed of 300 rpm during 120 minute with stream of nitrogen gas (N2) as inert gas. The result obtained indicated that optimum yield obtained at 2% catalyst NiMo/clay as much as 9% of biomass that is equal to 51,102%. Physical properties test result obtained that is density (1,0429 gr/ml), viscosity (9,307 cSt), acid number (22,470 mg of NaOH/gr of sample) and flash point (53 oC) respectively. Result of chemical analysis with GC-MS, obtained the dominant chemical components in bio-oil are Cyclohexane, Cyclohexanone, Pentane, 1-Pentene, 2-Pentene.Keywords: Biomass, Bio-oil, Catalysts NiMo/clay, Pine Wood, Pyrolysis